PERANCANGAN KEAMANAN KUNCI PINTU MENGGUNAKAN RFID DAN ARDUINO (STUDI KASUS: KADIN TANGERANG SELATAN) - Yuyevin Zebua; Rahmawati (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Along with the rapid development of technology, to help human needs are increasingly being innovated. In particular, in tool design. The door is the most important part in a room. Especially in the office space. Companies or agencies have important archives and documents that must be secured, so it is necessary to lock the door with a double system security so that it doesn't happen, data theft, information leakage, people enter carelessly and rooms are broken. So in this implementation the researchers designed a door lock device using Radio Frequency Identification and Arduino as a substitute for conventional keys. This system reads RFID Reader cards tag using the Arduino Mega 2560 module for input and output and uses a keypad with a dual system.